Effects of environmentally friendly soil remediation materials on soil quality and maize production (Bangladesh Journal of Botany, 2024)
In the precent, the reclaimed raw soil of newly renovated abandoned homestead was considered as the research object, and study the effects of different environmentally friendly soil remediation material combinations on the quality of reclaimed raw soil and maize crop production. A total of 6 improved material treatments were set up, including decomposed chicken manure(YJ), fly ash(FMH), ferrous sulfate curing agent(SHJ), ferrous sulfate curing agent+organic fertilizer (SYJ), fly ash+decomposed chicken manure(FYJ), and control treatment(CK). The research results showed that, the organic carbon content and water storage of new reclaimed raw soil exhibited a significant increasing trend after the application of different environmentally friendly modified materials(P < 0.05). Among them, the organic carbon and water storage of reclaimed soil under FYJ improved, which increased by 132.3 and 14.4 %, respectively compared with CK. During the growth period of summer maize, the plant height and yield exhibited a trend of FYJ> SYJ> YJ> FMH> SHJ> CK. The yield of maize under SYJ and FYJ treatments increased by 38.8 and 53.4 %, respectively, compared with CK. The appropriate combination of environmentally friendly soil remediation materials is helpful to improve the quality of new reclaimed raw soil, promote soil carbon sequestration, increase the comprehensive utilization rate of waste resources, increase the production performance of crops, and help rural revitalization and beautiful rural construction.Bangladesh J. Bot. 53(3): 673-679, 2024 (September) Special